2021
DOI: 10.1029/2020jc016889
|View full text |Cite
|
Sign up to set email alerts
|

Porites Calcifying Fluid pH on Seasonal to Diurnal Scales

Abstract: Coral resilience to ocean acidification is largely determined by the degree of physiological control corals can exert on their calcifying fluid carbonate chemistry. In this study, the boron isotopic composition (δ11B) of a Porites colony growing on a reef flat on Kiritimati Island in the equatorial central Pacific is examined to quantify the sensitivity of calcifying fluid pH (pHcf) to ambient environmental conditions. Skeletal δ11B along the growth axis of one annual growth band was determined with bulk analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…This mechanism was proposed in the GBR and Ningaloo Reef, Australia, where both DIC cf (Figures 2b, 3a, 3b, and S1b in Supporting Information ) and DIC cf /seawater dissolved inorganic carbon (DIC sw ) display a strong positive relationship with temperature (M. T. McCulloch et al., 2017). This pH seasonality is consistent amongst a wide range of reefs, including the GBR, Coral Sea, Western Australia, Caribbean, and Central Pacific (Chalk et al., 2021; D’Olivo & McCulloch, 2017; D’Olivo et al., 2019; Hemming et al., 1998; Knebel et al., 2021; M. T. McCulloch et al., 2017; Pelejero et al., 2005; Ross et al., 2019). However, all of these sites have fundamentally different dynamics than in the Galápagos, where the cool season experiences upwelling of DIC‐rich waters (Kessler, 2006, Figures 3a and 3b) that impacts the seasonality of CF chemistry.…”
Section: Resultssupporting
confidence: 52%
“…This mechanism was proposed in the GBR and Ningaloo Reef, Australia, where both DIC cf (Figures 2b, 3a, 3b, and S1b in Supporting Information ) and DIC cf /seawater dissolved inorganic carbon (DIC sw ) display a strong positive relationship with temperature (M. T. McCulloch et al., 2017). This pH seasonality is consistent amongst a wide range of reefs, including the GBR, Coral Sea, Western Australia, Caribbean, and Central Pacific (Chalk et al., 2021; D’Olivo & McCulloch, 2017; D’Olivo et al., 2019; Hemming et al., 1998; Knebel et al., 2021; M. T. McCulloch et al., 2017; Pelejero et al., 2005; Ross et al., 2019). However, all of these sites have fundamentally different dynamics than in the Galápagos, where the cool season experiences upwelling of DIC‐rich waters (Kessler, 2006, Figures 3a and 3b) that impacts the seasonality of CF chemistry.…”
Section: Resultssupporting
confidence: 52%
“…Large pH variability in the coral reef environment is often attributed to a set of competing processes like photosynthesis and respiration over seasonal‐diurnal timescales (Chen et al., 2015; DeCarlo et al., 2019; Knebel et al., 2021; Sevilgen et al., 2019). Several studies have demonstrated that the Net Ecosystem Calcification (NEC) and the Net Ecosystem Productivity (NEP) influence the diurnal pH variability of the reef environment (Andersson et al., 2014; DeCarlo, Cohen, et al., 2017; Fowell et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, the patterns of calcium transport in the axial canal and details of its structural transformation during coral growth remain obscure, as literature on this subject is scarce [24]. Meanwhile, although the transport of organic compounds within coral colonies has been suggested in various works, most are inferences based on markers or elemental measurements [25][26][27][28][29], rather than direct visualizations of structural changes in coral colonies. Errors may occur in the measurements, because of the requirement to remove tissue from the skeletons [30].…”
Section: Introductionmentioning
confidence: 99%